Adsorption Of Cd(II) Ions From Aqueous Solution By A Low-Cost Biosorbent Prepared From Ipomea Pes-Caprae Stem - Thaharah Ramadhani; Faisal Abdullah; Indra Indra; Abrar Muslim; Suhendrayatna Suhendrayatna; Hesti Meilina; Saiful Saiful (Aceh International Journal of Science and Technology, 2020)
The use of a low-cost biosorbent prepared from Ipomoea pes-caprae stem for the adsorption of Cd(II) ions from aqueous solution at different contact times, biosorbent sizes, pH values, and initial Cd(II) ions concentration solution was investigated. The biosorbent was analyzed using Fourier-transform infrared spectroscopy (FT-IR) to find important IR-active functional groups. A scanning electron microscope (SEM) was used to examine the biosorbent morphology. The experimental results showed the highest Cd(II) ions adsorption was 29.513 mg/g  under an optimal condition as initial Cd(II) ions concentration of 662.77 mg/L, 1 g dose, 80-min contact time, pH 5, 75 rpm of stirring speed, 1 atm, and 30 oC. Cd(II) ions' adsorption kinetics obeys the linearized pseudo-second-order kinetics (R2 = 0.996), and the adsorption capacity is based on the optimal condition, and the rate attained was 44.444 mg/g and 0.097 g/mg. Min, respectively. Besides, the adsorption isotherms were very well fitted by the linearized Langmuir isotherm model, and the monolayer adsorption capacity and pore volume determined was 30.121 mg/g and 0.129 L/mg, respectively. These results indicated the chemisorption nature